DENTAL CARIES IN GEZIRA PROVINCE - Yousif, Mugahid Abd El Rahman (Gezira Journal of Health Sciences; Vol 3 No 1 (2007), 2007)
Objectives :      The present study was aimed: To update information on the present status and prevalence of dental caries disease. To assess the oral health situation of the study area by assessing the dental caries prevalence: i.e. DMFT & DMFS formulate strategy and policy for promoting dental health services aiming at achieving a good standards of oral health to attain appropriate reduction in dental caries prevalence.